PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, DAN BUDAYA ETIS ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) AKUNTANSI (Studi Empiris Pada SKPD Kabupaten Kampar) - Aisah Fachrunisa; Amir Hasan; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted to examine the effect of variable effectiveness of internal controls, distributive justice, procedural justice, and organization’s ethic culture on the fraud tendency of accounting in local work unit in kampar regency. Collecting data using questionnaires. Data of this research obtained from head and staff of accounting. Of the 96 questionnaires distributed, the number of returnees is 90 questionnaire and a questionnaire that can be processed a number of 86 questionnaires. Data were analyzed by using multiple regression (multiple regression) with the help of a computer program SPSS version 17.0. The results showed that the effectiveness of internal control and organization’s ethic culture influence on the fraud tendency of accounting. there is no effect among distributive justice and procedural justice on the fraud tendency of accounting.Keywords: effectiveness, control, justice, culture, and fraud